(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The state of the state of the Kyrgyz people in the XIX - early. The 20th century is one of the most vague moments in our history. In Soviet historiography, the history of the state of the majority of peoples was treated superficially, so this situation was mostly not disclosed. Moreover, since the study of the history of nomads in the past was dominated by a Eurocentric view, there are erroneous views that during this period the Kyrgyz people were divided into tribes and could not pursue a single state policy and did not become the sovereign of their own state. Of course, at that time, the vast majority of the Kyrgyz led a nomadic lifestyle, but their oral creativity and culture, passed down from generation to generation, is priceless. This article (Kokon Khanate and the periods of the colonial policy of Russia) reflects the activities of famous people during the period of the Kokon Khanate (19th century): Medet Datka, Taylak baatyr, Nuzup Biy, Ormon Khan, Alymbek Datka, Alymkul Lashker reflected in the folk oral produced cats of the Kyrgyz as folklore source. Prominent representatives of the Kyrgyz community who lived during the period of Russian colonial policy (early twentieth century): Kurmanzhan Datka, Borombay Biy, Shabdan Bogatyr, Iskhak Asan uulu, Mamyr Mergen uulu, Abdyldabek, Moldo Ashir and other activities of individuals, historical events, national The liberation struggle was reflected in the sources of oral works that were passed down from generation to generation.